(untitled) (Journal of Environmental Science and Natural Resources, 2017)
An experiment was conducted at the Moinar Mor Sabuj Nursery, Mymensingh to evaluate the effects of compost prepared from solid wastes of Mymensingh municipality area on the yield and yield attributes of three crops viz. Chilli, Dahlia and Marigold grown in pots. Each crop was grown under six different treatments viz. 100% compost (T0), 75% compost + 25% soil (T1), 50% compost + 50% soil (T2), 25% compost + 75% soil (T3), 100% soil (T4) and farmers practice- (T5) (75% of recommended rate of NPK plus soil). A single factor experiment was laid out in a with three replications. The results revealed that in Chilli, application of 75% compost plus 25% soil (T1) produced significantly the tallest plant (45.50 cm), maximum number of flowers (25.00) and fruits (21.00) plant-1, longest leaf (11.67 cm), longest root (5.43 cm) and greater yield of fruits plant-1 (168.30 g). This treatment also produced the tallest plant (45.33 cm), maximum flowers plant-1 (2.33), longest leaf (11.55 cm) and higher fresh weight of single flower (7.34 g) of Dahlia. Compost treatment also significantly influenced various plant characters of Marigold where 75% compost + 25% soil (T1) gave the tallest plant (16.33 cm), higher weight of fresh flower (10.52 g), longest leaf (10.10 cm) and maximum flowers plant-1 (16.33). Plants grown in 100% compost showed the longest duration in case of Dahlia (19 days) and Marigold (23 days) flowering. From the findings, it can be inferred that use of 75% compost prepared from solid wastes of Mymensingh municipality area plus 25% soil appeared to be the best practice for obtaining the maximum yield of Chilli, Dahlia and Marigold. J. Environ. Sci. & Natural Resources, 10(1): 149-155 2017